Distribution, characterization, and evolution of heavy metal resistance genes and Tn7-like associated heavy metal resistance Gene Island of Burkholderia - Lan, Yanhong; Liu, Meijia; Song, Yao; Cao, Yu; Li, Fosheng; Luo, Dening; Qiao, Dairong (Frontiers in Microbiology, 2023)
Burkholderia is a rod-shaped aerobic Gram-negative bacteria with considerable genetic and metabolic diversity, which can be used for bioremediation and production applications, and has great biotechnology potential. However, there are few studies on the heavy metal resistance of the Burkholderia genus. In this paper, the distribution, characteristics and evolution of heavy metal resistance genes in Burkholderia and the gene island of Tn7-like transposable element associated with heavy metal resistance genes in Burkholderia were studied by comparative genomic method based on the characteristics of heavy metal resistance. Firstly, the classification status of some species of the Burkholderia genus was improved, and it was found that Burkholderia dabaoshanensis and Burkholderia novacaledonica do not belong to the Burkholderia genus. Secondly, comparative genomics studies and pan-genome analysis found that the core genome of Burkholderia has a larger proportion of heavy metal resistance genes and a greater variety of heavy metal resistance genes than the subsidiary genome and strain specific genes. Heavy metal resistance genes are mostly distributed in the genome in the form of various gene clusters (for example, mer clusters, ars clusters, czc/cusABC clusters). At the same time, transposase, recombinase, integrase and other genes were found upstream and downstream of heavy metal gene clusters, indicating that heavy metal resistance genes may be obtained through horizontal transfer. The analysis of natural selection pressure of heavy metal resistance genes showed that heavy metal resistance genes experienced strong purification selection under purification selection pressure in the genome. The Tn7 like transposable element of Burkholderia was associated with the heavy metal resistance gene island, and there were a large number of Tn7 transposable element insertion events in genomes. At the same time, BGI metal gene islands related to heavy metal resistance genes of Tn7 like transposable element were found, and these gene islands were only distributed in Burkholderia cepacia, Burkholderia polyvora, and Burkholderia contaminant. Understanding the resistance of the Burkholderia genus to heavy metals and the structure and characteristics of heavy metal islands in the genome is crucial for subsequent theoretical research and environmental adaptation of the genus.